In vitro activity of tigecycline and colistin against A. baumannii clinical bloodstream isolates during an 8-year period. (October 2015) - Spiliopoulou, Anastasia; Jelastopulu, Eleni; Vamvakopoulou, Sofia; Bartzavali, Christina; Kolonitsiou, Fevronia; Anastassiou, Evangelos D.; Christofidou, Myrto
<x content-type="archive" xml:space="preserve">Abstract</x> Acinetobacter baumannii has emerged as an important and problematic pathogen causing bloodstream infections (BSI) in hospitalized patients. Results of an 8-year period from a university hospital are presented. Identification of A. baumannii was performed by Gram-negative BD BBL Crystal ID and VITEK®2 system, whereas, susceptibility testing by VITEK2, Kirby–Bauer disc system, and Etest strips. Interpretation of results was based on CLSI criteria and, regarding tigecycline, Food and Drug Administration (FDA) criteria. Between 2006 and 2013, 441 among 7088 BSI cases were attributed to A. baumannii. Of all isolates, 92·1% were resistant to more than three classes of antibiotics and 79·4% were resistant to all but one or two categories of antimicrobials. Resistance to ampicillin–sulbactam, meropenem, gentamicin, ciprofloxacin, minocycline, and tigecycline increased during the study period (P<0·05). Although tigecycline resistance was low during the first 4 years of the study (25·5%), it increased up to 66·5% during 2010–2013. No isolate was colistin resistant.